Regulatory T cells (CD4+CD25+FOXP3+) in lupus nephritis - Mohd Kamil, Mohd Khairul; Mohd, Rozita; Abdul Cader, Rizna; Ithnin, Azlin; Mohd Shah, Shamsul Azhar (International Journal of Research in Medical Sciences, 2018)
Background: Systemic lupus erythromatosus (SLE) is an autoimmune disease with 20–65% of patients developing lupus nephritis (LN). Studies have reported 10% of LN patients will end up with end stage renal disease and their mortality rate is higher compared to patients without LN. Abnormality of regulatory T cells (Tregs) level is thought to be a potential factor for this LN development. The aim of study was to evaluate the percentage of Tregs in LN patients. Methods: This was a comparative cross sectional study involving LN patients and age and gender matched controls with a 2:1 ratio. The patients were grouped into active and inactive LN based on their lupus activity index; complement levels, ANA, dsDNA antibodies, ESR, SLE Disease Activity Index (SLEDAI2K) score and also urine PCI (uPCI>0.05 for active group). Disease history, demographic data, routine blood test, peripheral blood for differentials count were taken and recorded. Peripheral blood mononuclear cells were stained with CD4, CD25 and Foxp3 antibodies and percentage of Tregs was analysed using BD fluorescence-activated cell sorting (FACS) cytometer. We compared demographic and laboratory parameters between healthy controls and LN patients as well as active and inactive LN patients. Results: A total of 34 LN patients (32 females, 2 males) were recruited. Their mean age and disease duration were 37.97±11.14 years and 110.95±65.07 months respectively. Thirteen matched controls with mean age 35.23±7.89 years were enrolled. There was no demographic difference between 2 groups of LN patients. Tregs were significantly lower in active LN compared to inactive LN and healthy control (0.44±0.37% vs. 1.89±0.46% vs. 3.12±0.56% of the CD4+, P<0.001). C3 and C4 complement fragments were significantly reduced in patients with active disease (C3; 50.92±28.43 vs. 76.31±25.63, P=0.011) and (C4; 11.17±8.41 vs. 16.70±6.50 P=0.044). Proteinuria was significantly higher while serum albumin levels were significantly lower in active patients compared to inactive patients and healthy control (urine PCI; 0.25(0.15-0.3) vs. 0.03(0.01-0.05) vs. 0.01, P<0.001) and (albumin; 29.89±6.87 vs. 36.87±3.58 vs. 40.62±1.89mmol/L, P<0.001). We found positive inversely correlation between Tregs with SLEDAI2K (r = -0.572, P=0.011) and proteinuria (r = -0.451, P=0.007). Conclusions: Tregs, C3 and C4 complements, and albumin were significantly lower while proteinuria was significantly higher in active LN. There was positive inversely correlation between the percentage of Tregs with SLEDAI2K score and proteinuria.